1995
DOI: 10.1016/1074-7613(95)90009-8
|View full text |Cite
|
Sign up to set email alerts
|

In the absence of a CD40 signal, B cells are tolerogenic

Abstract: When B cells are deprived of signaling through CD40, they exhibit the ability to induce T cell tolerance. The in vivo administration of anti-gp39 and allogeneic B cells diminished the ability of mice to mount an allogeneic response. Tolerance induction was specific for the haplotype expressed on the allogeneic B cells. Selective allospecific unresponsiveness was induced in the CD8 and CD4 compartments by the administration of anti-gp39 and class II-deficient B cells or class I-deficient B cells, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 29 publications
5
81
0
Order By: Relevance
“…Longterm cardiac alloengraftment was also achieved in 75% of mice after transient administration of anti-CD154 (versus 0% in the control group) [45], and brief treatment with this antibody after transplantation of allogeneic pancreatic islet cells induced indefinite graft survival in approximately 40% of the treated mice and delayed rejection in the remaining recipients, whereas all of the control mice rejected at day 15 [46]. Furthermore, prior transfusion of the recipients with donor lymphocytes (donor-specific transfusion, DST) along with anti-CD154 lead to long-term islet cell survival in 96% of the mice in this study [46], consistent with the observation that allogeneic B cells are a powerful tolerigen if not activated through CD40 [43,44]. Finally, renal allograft rejection in rhesus monkeys was also prevented out to approximately 100 days by transient administration of anti-CD154, at which time re-treatment with the antibody inhibited the rejection process [47].…”
Section: Tolerance Induction To Alloantigensupporting
confidence: 73%
See 2 more Smart Citations
“…Longterm cardiac alloengraftment was also achieved in 75% of mice after transient administration of anti-CD154 (versus 0% in the control group) [45], and brief treatment with this antibody after transplantation of allogeneic pancreatic islet cells induced indefinite graft survival in approximately 40% of the treated mice and delayed rejection in the remaining recipients, whereas all of the control mice rejected at day 15 [46]. Furthermore, prior transfusion of the recipients with donor lymphocytes (donor-specific transfusion, DST) along with anti-CD154 lead to long-term islet cell survival in 96% of the mice in this study [46], consistent with the observation that allogeneic B cells are a powerful tolerigen if not activated through CD40 [43,44]. Finally, renal allograft rejection in rhesus monkeys was also prevented out to approximately 100 days by transient administration of anti-CD154, at which time re-treatment with the antibody inhibited the rejection process [47].…”
Section: Tolerance Induction To Alloantigensupporting
confidence: 73%
“…Despite the fact that the injected DCs expressed high levels of MHC Class I, MHC Class II, as well as both B7.1 and B7.2 on their surface, allogeneic helper (cytokine production) and cytotoxic T cell responses were found to be greatly diminished in the CD154-deficient mice [unpublished results]. It is not yet clear whether DCs deprived of CD40 maturation signals are actively tolerigenic toward T cells, as has been described for resting B cells [43,44]. However, these data indicate that CD40/CD154 costimulation that occurs in the context of helper T cell/DC cognate interaction is critical for the acquistion of DC antigen-presenting capabilities.…”
Section: The Role Of Cd40 In DC Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…In other models of tolerance, B cells induce CD8 ϩ suppressor T cells when peptides are presented in the context of the nonclassical class I molecule Qa-1 (10). Coupled with other studies showing that B cells can serve as tolerogenic APC (11)(12)(13)(14)(15)(16), these results suggested that the B cell might present Ag in the ACAID spleen.…”
mentioning
confidence: 72%
“…Indeed, treatment with anti-CD154 mAb diminished the response to alloantigen on B cells in vitro (18), whereas immunization with resting B cells from CD154 Ϫ/Ϫ mice induced tolerance to alloantigen (19). Treatment with anti-CD154 mAb blocks both primary and secondary immune responses to T cell-dependent Ags, as well as the development of germinal centers and the generation of memory cells (20).…”
Section: Discussionmentioning
confidence: 99%